Oct4 overexpression facilitates proliferation of porcine fibroblasts and development of cloned embryos. Issue 5 (October 2015) - Kim, Su Jin; Koo, Ok Jae; Park, Hee Jung; Moon, Joon Ho; da Torre, Bego Roibas; Javaregowda, Palaksha Kanive; Kang, Jung Taek; Park, Sol Ji; Saadeldin, Islam M.; Choi, Ji Yei; Lee, Byeong-Chun; Jang, Goo
Summary Octamer-binding transcription factor 4 (Oct4) is a critical molecule for the self-renewal and pluripotency of embryonic stem cells. Recent reports have shown that Oct4 also controls cell-cycle progression and enhances the proliferation of various types of cells. As the high proliferation of donor fibroblasts is critical to the production of transgenic pigs, using the somatic cell nuclear transfer technique, we analysed the effect of Oct4 overexpression on the proliferation of porcine fibroblasts and embryos. Porcine endogenous Oct4 cDNA was cloned, sequenced and inserted into an expression vector. The vector was transfected into porcine fibroblasts, and a stable Oct4-overexpressed cell line was established by antibiotic selection. Oct4 expression was validated by the immunostaining of Oct4. Cell morphology was changed to sharp, and both proliferation and migration abilities were enhanced in Oct4-overexpressed cells. Real-time RT-PCR results showed that p16, Bcl2 and Myc were upregulated in Oct4-overexpressed cells. Somatic cell nuclear transfer was performed using Oct4-overexpressed cells, and the development of Oct4 embryos was compared with that of wild-type cloned embryos. The cleavage and blastocyst formation rates were improved in the Oct4 embryos. Interestingly, blastocyst formation of the Oct4 embryos was observed as early as day 5 in culture, while blastocysts were observed from day 6 in wild-type cloned embryos. In conclusion, the overexpression of Oct4 enhanced the proliferation of both porcine fibroblasts and embryos.